A new species, Aster yaoshanensis (Asteracae, Astereae), from Guangxi (China), based on morphology and molecular phylogenetic data - Zheng, Xinyi; Qin, Kun; Li, Tingyu; Qu, Tianmeng; Luo, Junjia; Zhang, Guojin; Li, Bo; Li, Pan; Fu, Zhixi (Frontiers in Plant Science, 2024)
Aster yaoshanensis sp. nov., a new species of the family Asteraceae is here described and illustrated. The species is presently known only from rock crevices of mountain valleys in Dayaoshan National Nature Reserve, Guangxi autonomous region, China. Phylogenetic analyses based on ITS sequences and complete plastome data have shown that this new species is a member of genus Aster with high support. Morphologically, it mostly resembles A. jishouensis, but it can be easily distinguished from the latter by bract indumentum (glabrous except margin ciliate vs. villous especially on veins abaxially, glabrous adaxially) and color (green vs. purple), shorter corolla (3.2–3.5 mm vs. 4.5–5.3 mm), bract stalk (obvious, ca.1.2 mm vs. sessile), and different distribution (Guangxi vs. Hunan). The detailed description, distribution map, and photos are provided. This study further elucidates the species identification, phylogeny and characteristic evolution of Aster.